Inside a corporate affairs conference: the race for a social license - Cullerton, Katherine; Patay, Dori (Frontiers in Communication, 2024)
Introduction A consequence of corporate influence on public policy is the potential for negative impacts on population health. Consequently, it is imperative that public health advocates and scholars stay abreast of emerging corporate practices designed to influence regulatory measures aimed at safeguarding health. To identify these emerging practices, we attended a national corporate affairs conference to identify tactics and gain insights from the range of commercial actors presenting at the event. Method An observational design was used for the research. This involved observation of senior executives presenting at a national corporate affairs conference in Australia in 2023. The collected data was inductively and thematically analyzed by the authors. Results Our findings revealed that the foremost concern for corporations was maintaining a “social license to operate.” Notably, corporate actors perceived social media as a critical threat to social license as it can rapidly sway public opinion against them. Strategies identified for preserving social license included building relationships with the public and civil society, leveraging AI-driven data services to monitor and effectively respond to perceived threats, to convert dissenters into advocates, and applying the narrative of value creation and stakeholder capitalism. Conclusion This study contributes valuable insights for public health advocates and scholars by shedding light on the mechanisms employed by corporations to counteract regulatory measures. These mechanisms include using stakeholder capitalist narratives to frame and reframe discussion and debate, engaging dissenters to convert them into advocates, and leveraging partnerships to camouflage actions and build social license halos. It also revealed the unprecedented power and new platforms that previously weak actors now have via social media. The observations from the conference offer a nuanced understanding of corporate strategies, enabling advocates to effectively challenge prevailing narratives that may undermine public health initiatives.